(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Soap noodles are the primary intermediate raw material used in the manufacture of toilet soaps and bathing bars worldwide. Their uniform chemical composition, physical consistency, and controlled quality enable manufacturers to formulate soaps with desired cleansing efficiency, mildness, and aesthetic appeal. The toilet soap industry plays a crucial role in maintaining personal hygiene and public health while contributing significantly to the chemical and consumer goods sector. This journal paper presents a comprehensive review of soap noodles and toilet soaps, focusing on their raw materials, chemical composition, manufacturing processes, quality control parameters, finished product specifications, industrial applications, and environmental considerations. Emphasis is given to Total Fatty Matter (TFM), process standardization, and sustainability aspects relevant to modern soap manufacturing.